Remarkable decrease in the viscosity of waxy crude oil under an electric field. Issue 47 (21st October 2020) - Jain, Ankita; Seth, Jyoti R.; Juvekar, Vinay A.; Verma, Nidhi; Pandey, Nandini
Abstract : Liquefaction of the wax network in crude oil by an electric field. Abstract : Uninterrupted transport of waxy crude oil through pipelines remains a pressing concern for the petroleum industry. When the ambient temperature falls below the pour point of the crude, deposition of wax particles may lead to complete blockage of the pipeline. We demonstrate that the application of a DC electric field to waxy crude below its pour point can effectively break the wax network and also reduce the viscosity by up to two orders of magnitude. We have studied the dynamics of the change in viscosity during and after application of an electric field. Three regimes are observed. First is the induction regime, where viscous stresses dominate and the viscosity remains unchanged. During the intermediate and final regimes, the decrease in viscosity follows first order kinetics with rate constants proportional to the strength of the electric field and to the square of the strength, respectively. Microscopic evidence shows that some network connections break during the intermediate regime, whereas in the final regime, further fragmentation of the pieces of the broken network occurs. This is accompanied by aggregation of fine wax fragments. After cessation of the field, the viscosity increases gradually. The rate and the extent of recovery of viscosity depend only on the value of viscosity at the point of cessation of the field. That the breakage of the network occurs, even in the absence of shear, has been demonstrated. Through measurement of the dielectric constants and conductivities of the crude oil and its component phases, we have shown that the wax network experiences compressive Maxwell stress, which is dominated by the electric field within the wax particles.